The Influence of Islamic Leadership on Work Performance in Service Industry: An Empirical Analysis - Zaim, Halil; Erzurum, Erdem; Zaim, Selim; Uluyol, Burhan; Seçgin, Gökhan; Uluyol, Burhan (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose - This study aims to propose a practical, virtue-centric model of leadership based on Islamic principles. The structure of the Islamic leadership construct is validated through confirmatory factor analysis. Its relationship with performance and organizational commitment is examined and the mediating role of organizational commitment is assessed. Design/methodology/approach - Islamic leadership model is tested using confirmatory factor analysis with data collected from employees working in the services sector in Turkey. Relationships between Islamic leadership, organizational commitment and performance are examined through a path analysis. Findings - The factor analysis results presented a good fit for the proposed Islamic leadership model, which consists of wisdom, religiosity, justice and kindness dimensions. Regarding path analysis, findings indicated a positive relationship between Islamic leadership and job performance. Moreover, organizational commitment partially mediated the relationship between Islamic leadership and job performance. Originality/value - Previous studies on Islamic leadership contain a very little number of empirical models. This study proposes a valuable empirical model of Islamic leadership consisting of moral values, spirituality, ethics and wisdom. In addition, the proposed model is supported with empirical pieces of evidence. Evidence of the partial mediating role of organizational commitment between Islamic leadership and job performance is also revealed by the study.
The authors are deeply grateful to Professor Sebastian Berger (the editor) and the anonymous reviewer for his or her valuable comments which improved the quality of the article greatly. The remaining errors and mistakes belong to authors.
Keywords: Islamic leadership; Leadership; Job performance; Organizational commitment; Islamic values; Islamic work ethics